Tindakan Agronomi dan Produktivitas Kebun Kakao Rakyat di Desa Betung, Kecamatan Kumpeh Ilir, Kabupaten Muaro Jambi - Nengsih, Yulistiati; Nasamsir, Nasamsir; Adistya, Adilla; Andriyani, Lizyanti; Daulay, Muhammad Ferdinan Iko (Universitas Batanghari, 2025)
Low cocoa productivity, especially in smallholder plantations, is caused by soil conditions showing symptoms of